Morfofisiologia do capim-tamani irrigado sob doses de nitrogênio - Vasconcelos, Elayne Cristina Gadelha (2018)
The availability of nutrients associated with forage species of high biomass production are essential to the success of animal productivity in pastures. In this perspective, the release of new and more efficient cultivars, such as tamani grass, appears as an alternative to make pasture production systems less susceptible to production seasonality. The goal of this study was to evaluate the gas exchange, biomass flow, structural characteristics, biomass components and growth rates of tamani grass subjected to different nitrogen doses (0, 300, 600 and 1200 kg ha-1 year-1). For analysis of biomass flow, structural characteristics and biomass components, a randomized complete block design with three replications was used. For the variables of gas exchange and growth indices, a split plot randomized complete block design was used, with the nitrogen doses assigned to the plots and the number of new leaves produced to the subplots, with three replications. The evaluations were performed in the rest period of the pasture after defoliation to a residual leaf area index (LAI) of 1.0 and until the moment that pasture reached a number of new leaves produced per tiller (NNF) of 3.0, ending the regrowth period. There was a positive interaction between nitrogen doses and NNF for leaf temperature, leaf transpiration rate, stomatal conductance, net photosynthesis rate, instantaneous carboxylation efficiency and relative chlorophyll index. The highest leaf transpiration (4.74 mmol m-2 s-1) was recorded at the dose 999.2 kg ha-1 year-1 with NNF of 2.4. The maximum net photosynthesis was 25.3 μmol m-2 s-1, recorded at the dose 871.3 kg ha-1 year-1 with NNF of 2.3. There was no interaction between nitrogen doses and NNF for any of the vegetative growth variables. The highest growth rate (56.9 g m-2 day-1) was observed at the dose 1,200 kg ha-1 year-1 with NNF of 1.8. The maximum relative growth rate was 0.12 g g 1day-1, at the dose 1,200 kg kg ha-1 year-1 and NNF of 1.0. There was a higher value for TAL (6.0 g m-2 day-1) at the dose 1,200 kg N ha-1 year-1 and NNF of 1.0. Leaf and stem elongation rates, forage yield and accumulation rates increased up to 1,200 kg N ha-1 year-1. There was a decreasing linear response for phyllochron and leaf life span, providing a reduction of 0.037 and 0.00815 days, respectively, per kilogram of nitrogen. The previous leaf senescence rates were not influenced by nitrogen fertilization, with mean values equal to 0.363 + 0.100 cm tiller-1 day-1. We found an increasing linear response with the increase in nitrogen doses for: cumulative total forage biomass, green forage biomass, green leaf blade biomass, tiller population density, sward height, leaf area index and interception of photosynthetically active radiation. Nitrogen fertilization with up to 1,200 kg ha-1 year-1 promotes positive responses on the gas exchange and the morphophysiology of tamani grass.